Video Head Impulse Test Findings in Patients With Benign Paroxysmal Positional Vertigo Secondary to Idiopathic Sudden Sensorineural Hearing Loss - Liu, Yingzhao; Leng, Yangming; Zhou, Renhong; Liu, Jingjing; Wang, Hongchang; Xia, Kaijun; Liu, Bo; Xiao, Hongjun (Frontiers in Neurology, 2022)
Benign paroxysmal positional vertigo (BPPV) is amongst the most common causes of episodic vestibular syndrome. It can be classified as idiopathic and secondary types according to the causative factors, and the underlying mechanism between idiopathic (i-BPPV) and secondary BPPV (s-BPPV) may differ. Idiopathic sudden sensorineural hearing loss (ISSNHL) has been considered as a common inner ear disease that precipitates s-BPPV. Yet, few studies have addressed the functional impairment of the semicircular canal (SCC) system in patients with s-BPPV associated with ISSNHL. Our purpose was to explore the pathophysiological mechanism and investigate the clinical implications of video head impulse test (vHIT) in these patients. Here, the clinical and laboratory data of patients with BPPV secondary to ISSNHL, including the results of vHIT, were retrospectively reviewed, and compared with those of patients with i-BPPV. Pathological vHIT findings (low vestibulo-ocular reflex gain and re-fixation saccade), which mainly affected the posterior SCC, were more common in the s-BPPV group than in the i-BPPV group (41.9 and 0%, respectively). The incidence of horizontal SCC involvement was also higher in the s-BPPV group (45.16 and 16.67%, respectively). Furthermore, patients with s-BPPV showed lower vHIT gains of the posterior and horizontal SCCs in affected ears than in unaffected ears. Compared to i-BPPV, posterior SCC paresis detected by vHIT is more prevalent in BPPV secondary to ISSNHL. This dysfunction may be associated mainly with vestibular impairments caused by ISSNHL, and not with BPPV per se.